Elevation Data for Floodplain Mapping - National Research Council (The National Academies Press, 2007)
Floodplain maps serve as the basis for determining whether homes or buildings require flood insurance under the National Flood Insurance Program run by the Federal Emergency Management Agency (FEMA). Approximately $650 billion in insured assets are now covered under the program. FEMA is modernizing floodplain maps to better serve the program. However, concerns have been raised as to the adequacy of the base map information available to support floodplain map modernization. Elevation Data for Floodplain Mapping shows that there is sufficient two-dimensional base map imagery to meet FEMA's flood map modernization goals, but that the three-dimensional base elevation data that are needed to determine whether a building should have flood insurance are not adequate. This book makes recommendations for a new national digital elevation data collection program to redress the inadequacy. Policy makers; property insurance professionals; federal, local, and state governments; and others concerned with natural disaster prevention and preparedness will find this book of interest.
Keywords: Earth Sciences

The Grid: A Journey Through the Heart of Our Electrified World - Phillip F. Schewe (The National Academies Press, 2007)
The electrical grid goes everywhere -- it's the largest and most complex machine ever made. Yet the system is built in such a way that the bigger it gets, the more inevitable its collapse. Named the greatest engineering achievement of the 20th century by the National Academy of Engineering, the electrical grid is the largest industrial investment in the history of humankind. It reaches into your home, snakes its way to your bedroom, and climbs right up into the lamp next to your pillow. At times, it almost seems alive, like some enormous circulatory system that pumps life to big cities and the most remote rural areas. Constructed of intricately interdependent components, the grid operates on a rapidly shrinking margin for error. Things can -- and do -- go wrong in this system, no matter how many preventive steps we take. Just look at the colossal 2003 blackout, when 50 million Americans lost power due to a simple error at a power plant in Ohio; or the one a month later, which blacked out 57 million Italians. And these two combined don't even compare to the 2001 outage in India, which affected 226 million people. The Grid is the first history of the electrical grid intended for general readers, and it comes at a time when we badly need such a guide. As we get more and more dependent on electricity to perform even the most mundane daily tasks, the grid's inevitable shortcomings will take a toll on populations around the globe. At a moment when energy issues loom large on the nation's agenda and our hunger for electricity grows, The Grid is as timely as it is compelling.
Keywords: Energy and Energy Conservation; Explore Science

Improving the Social Security Representative Payee Program: Serving Beneficiaries and Minimizing Misuse - National Research Council (The National Academies Press, 2007)
More than 7 million recipients of Social Security benefits have a representative payee—a person or an organization—to receive or manage their benefits. These payees manage Old Age, Survivors and Disability Insurance funds for retirees, surviving spouses, children, and the disabled, and they manage Supplemental Security Income payments to disabled, blind, or elderly people with limited income and resources. More than half of the beneficiaries with a representative payee are minor children; the rest are adults, often elderly, whose mental or physical incapacity prevents them from acting on their own behalf, and people who have been deemed incapable under state guardianship laws. The funds are managed through the Representative Payee Program of the Social Security Administration (SSA). The funds total almost $4 billion a month, and there are more than 5.3 million representative payees. In 2004 Congress required the commissioner of the SSA to conduct a one-time survey to determine how payments to individual and organizational representative payees are being managed and used on behalf of the beneficiaries.1 To carry out this work, the SSA requested a study by the National Academies, which appointed the Committee on Social Security Representative Payees. This report is the result of that study. Improving the Social Security Representative Payee Program: Serving Beneficiaries and Minimizing Misuse (1) assesses the extent to which representative payees are not performing their duties in accordance with SSA standards for representative payee conduct, (2) explains whether the representative payment policies are practical and appropriate, (3) identifies the types of representative payees that have the highest risk of misuse of benefits, and (4) finds ways to reduce the risk of misuse of benefits and ways to better protect beneficiaries.
Keywords: Behavioral and Social Sciences; Industry and Labor

Cancer in Elderly People: Workshop Proceedings - Institute of Medicine (The National Academies Press, 2007)
A high proportion of cancer occurs primarily in older persons, and incidence of the major cancers is greater. This, combined with the expansion of an aging America, is bound to have far reaching effects on the nation's healthcare industry. This summary of a workshop held in October 2006, reviews the various important implications of changing demographics and the cancer disease burden in the United States.
Keywords: Health and Medicine

A 21st Century System for Evaluating Veterans for Disability Benefits - Institute of Medicine (The National Academies Press, 2007)
21st Century System for Evaluating Veterans' Disability Benefits recommends improvements in the medical evaluation and rating of veterans for the benefits provided by the Department of Veterans Affairs (VA) to compensate for illnesses or injuries incurred in or aggravated by military service. Compensation is a monthly cash benefit based on a rating schedule that determines the degree of disability on a scale of 0 to 100. Although a disability rating may also entitle a veteran to ancillary services, such as vocational rehabilitation and employment services, the rating schedule is out of date medically and contains ambiguous criteria and obsolete conditions and language. The current rating schedule emphasizes impairment and limitations or loss of specific body structures and functions which may not predict disability well. 21st Century System for Evaluating Veterans' Disability Benefits recommends that this schedule could be revised to include modern concepts of disability including work disability, nonwork disability, and quality of life. In addition to the need for an updated rating schedule, this book highlights the need for the Department of Veterans' Affairs to devote additional resources to systematic analysis of how well it is providing services or how much the lives of veterans are being improved, as well as the need for a program of research oriented toward understanding and improving the effectiveness of its benefits programs.
Keywords: Health and Medicine

Tools and Methods for Estimating Populations at Risk from Natural Disasters and Complex Humanitarian Crises - National Research Council (The National Academies Press, 2007)
Worldwide, millions of people are displaced annually because of natural or industrial disasters or social upheaval. Reliable data on the numbers, characteristics, and locations of these populations can bolster humanitarian relief efforts and recovery programs. Using sound methods for estimating population numbers and characteristics is important for both industrialized and developing nations. Ensuring that the data are geographically referenced for projection onto maps is essential. However, good data alone are insufficient. Adequate staff training and strong organizational and political desire to maintain and use the information are also required. Tools and Methods for Estimating Populations at Risk from Natural Disasters and Complex Humanitarian Crises, reviews the main methods and tools for making estimates of subnational populations and makes several recommendations to improve the collection and the use of population data for emergency response and development.
Keywords: Behavioral and Social Sciences; Earth Sciences; Conflict and Security Issues

Informing the Future: Critical Issues in Health: Fourth Edition - Institute of Medicine (The National Academies Press, 2007)
Keywords: Health and Medicine

Green Healthcare Institutions: Health, Environment, and Economics: Workshop Summary - Institute of Medicine (The National Academies Press, 2007)
Green Healthcare Institutions : Health, Environment, and Economics, Workshop Summary is based on the ninth workshop in a series of workshops sponsored by the Roundtable on Environmental Health Sciences, Research, and Medicine since the roundtable began meeting in 1998. When choosing workshops and activities, the roundtable looks for areas of mutual concern and also areas that need further research to develop a strong environmental science background. This workshop focused on the environmental and health impacts related to the design, construction, and operations of healthcare facilities, which are part of one of the largest service industries in the United States. Healthcare institutions are major employers with a considerable role in the community, and it is important to analyze this significant industry. The environment of healthcare facilities is unique; it has multiple stakeholders on both sides, as the givers and the receivers of care. In order to provide optimal care, more research is needed to determine the impacts of the built environment on human health. The scientific evidence for embarking on a green building agenda is not complete, and at present, scientists have limited information. Green Healthcare Institutions : Health, Environment, and Economics, Workshop Summary captures the discussions and presentations by the speakers and participants; they identified the areas in which additional research is needed, the processes by which change can occur, and the gaps in knowledge.
Keywords: Health and Medicine

The Future of Disability in America - Institute of Medicine (The National Academies Press, 2007)
The future of disability in America will depend on how well the U.S. prepares for and manages the demographic, fiscal, and technological developments that will unfold during the next two to three decades. Building upon two prior studies from the Institute of Medicine (the 1991 Institute of Medicine's report Disability in America and the 1997 report Enabling America), The Future of Disability in America examines both progress and concerns about continuing barriers that limit the independence, productivity, and participation in community life of people with disabilities. This book offers a comprehensive look at a wide range of issues, including the prevalence of disability across the lifespan; disability trends the role of assistive technology; barriers posed by health care and other facilities with inaccessible buildings, equipment, and information formats; the needs of young people moving from pediatric to adult health care and of adults experiencing premature aging and secondary health problems; selected issues in health care financing (e.g., risk adjusting payments to health plans, coverage of assistive technology); and the organizing and financing of disability-related research. The Future of Disability in America is an assessment of both principles and scientific evidence for disability policies and services. This book's recommendations propose steps to eliminate barriers and strengthen the evidence base for future public and private actions to reduce the impact of disability on individuals, families, and society.
Keywords: Health and Medicine

Green Schools: Attributes for Health and Learning - National Research Council (The National Academies Press, 2007)
Evidence has accumulated that shows that the quality of indoor environments can affect the health and productivity of adults and children. One consequence is that a movement has emerged to promote the design of schools that have fewer adverse environmental effects. To examine the potential of such design for improving education, several private organizations asked the NRC to review and assess the health and productivity benefits of green schools. This report provides an analysis of the complexity of making such a determination; and an assessment of the potential human health and performance benefits of improvements in the building envelope, indoor air quality, lighting, and acoustical quality. The report also presents an assessment of the overall building condition and student achievement, and offers an analysis of and recommendations for planning and maintaining green schools including research considerations.
Keywords: Health and Medicine; Environment and Environmental Studies

PTSD Compensation and Military Service - Institute of Medicine; National Research Council (The National Academies Press, 2007)
The scars of war take many forms: the limb lost, the illness brought on by a battlefield exposure, and, for some, the psychological toll of encountering an extremely traumatic event. PTSD Compensation and Military Service presents a thorough assessment of how the U.S. Department of Veterans Affairs evaluates veterans with possible posttraumatic stress disorder and determines the level of disability support to which they are entitled. The book presents a history of mental health disability compensation of military personnel and reviews the current compensation and pension examination procedure and disability determination methodology. It offers a number of recommendations for changes that would improve the fairness, consistency, and scientific foundation of this vital program. This book will be of interest and importance to policy makers, veterans affairs groups, the armed forces, health care organizations, and veterans themselves.
Keywords: Conflict and Security Issues; Health and Medicine

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 17, Transit-Oriented Development - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2007)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Traveler Response to Transportation System Changes, Chapter 17--Transit-Oriented Development explores the transit-oriented development (TOD) land use strategy and its transportation impacts in terms of regional context, land use mix, and primary transit mode. TOD generally refers to higher-density development, with pedestrian priority, located within easy walking distance of a major public transit station or stop.The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.
Keywords: Transportation and Infrastructure

Environmental Public Health Impacts of Disasters: Hurricane Katrina: Workshop Summary - Institute of Medicine (The National Academies Press, 2007)
Public health officials have the traditional responsibilities of protecting the food supply, safeguarding against communicable disease, and ensuring safe and healthful conditions for the population. Beyond this, public health today is challenged in a way that it has never been before. Starting with the 9/11 terrorist attacks, public health officers have had to spend significant amounts of time addressing the threat of terrorism to human health. Hurricane Katrina was an unprecedented disaster for the United States. During the first weeks, the enormity of the event and the sheer response needs for public health became apparent. The tragic loss of human life overshadowed the ongoing social and economic disruption in a region that was already economically depressed. Hurricane Katrina reemphasized to the public and to policy makers the importance of addressing long-term needs after a disaster. On October 20, 2005, the Institute of Medicine's Roundtable on Environmental Health Sciences, Research, and Medicine held a workshop which convened members of the scientific community to highlight the status of the recovery effort, consider the ongoing challenges in the midst of a disaster, and facilitate scientific dialogue about the impacts of Hurricane Katrina on people's health. Environmental Public Health Impacts of Disasters: Hurricane Katrina is the summary of this workshop. This report will inform the public health, first responder, and scientific communities on how the affected community can be helped in both the midterm and the near future. In addition, the report can provide guidance on how to use the information gathered about environmental health during a disaster to prepare for future events.
Keywords: Earth Sciences; Health and Medicine

Ethical and Legal Considerations in Mitigating Pandemic Disease: Workshop Summary - Institute of Medicine (The National Academies Press, 2007)
In recent public workshops and working group meetings, the Forum on Microbial Threats of the Institute of Medicine (IOM) has examined a variety of infectious disease outbreaks with pandemic potential, including those caused by influenza (IOM, 2005) and severe acute respiratory syndrome (SARS) (IOM, 2004). Particular attention has been paid to the potential pandemic threat posed by the H5N1 strain of avian influenza, which is now endemic in many Southeast Asian bird populations. Since 2003, the H5N1 subtype of avian influenza has caused 185 confirmed human deaths in 11 countries, including some cases of viral transmission from human to human (WHO, 2007). But as worrisome as these developments are, at least they are caused by known pathogens. The next pandemic could well be caused by the emergence of a microbe that is still unknown, much as happened in the 1980s with the emergence of the human immunodeficiency virus (HIV) and in 2003 with the appearance of the SARS coronavirus. Previous Forum meetings on pandemic disease have discussed the scientific and logistical challenges associated with pandemic disease recognition, identification, and response. Participants in these earlier meetings also recognized the difficulty of implementing disease control strategies effectively. Ethical and Legal Considerations in Mitigating Pandemic Disease: Workshop Summary as a factual summary of what occurred at the workshop.
Keywords: Health and Medicine

Putting People on the Map: Protecting Confidentiality with Linked Social-Spatial Data - National Research Council (The National Academies Press, 2007)
Precise, accurate spatial information linked to social and behavioral data is revolutionizing social science by opening new questions for investigation and improving understanding of human behavior in its environmental context. At the same time, precise spatial data make it more likely that individuals can be identified, breaching the promise of confidentiality made when the data were collected. Because norms of science and government agencies favor open access to all scientific data, the tension between the benefits of open access and the risks associated with potential breach of confidentiality pose significant challenges to researchers, research sponsors, scientific institutions, and data archivists. Putting People on the Map finds that several technical approaches for making data available while limiting risk have potential, but none is adequate on its own or in combination. This book offers recommendations for education, training, research, and practice to researchers, professional societies, federal agencies, institutional review boards, and data stewards.
Keywords: Computers and Information Technology

Earth Materials and Health: Research Priorities for Earth Science and Public Health - Institute of Medicine; National Research Council (The National Academies Press, 2007)
A range of natural earth materials, like arsenic or fluoride, have long been linked to significant human health effects. Improved understanding of the pervasive and complex interactions between earth materials and human health will require creative collaborations between earth scientists and public health professionals. At the request of the National Science Foundation, U.S. Geological Survey, and National Aeronautics and Space Administration, this National Research Council book assesses the current state of knowledge at the interface between the earth sciences and public health disciplines. The book identifies high-priority areas for collaborative research, including understanding the transport and bioavailability of potentially hazardous earth materials, using risk-based scenarios to mitigate the public health effects of natural hazards under current and future climate regimes, and understanding the health risks that result from disturbance of earth systems. Geospatial information - geological maps for earth scientists and epidemiological data for public health professionals - is identified as one of the essential integrative tools that is fundamental to the activities of both communities. The book also calls for increased data sharing between agencies to promote interdisciplinary research without compromising privacy.
Keywords: Earth Sciences; Environment and Environmental Studies

Preventing Medication Errors - Institute of Medicine (The National Academies Press, 2007)
In 1996 the Institute of Medicine launched the Quality Chasm Series, a series of reports focused on assessing and improving the nation's quality of health care. Preventing Medication Errors is the newest volume in the series. Responding to the key messages in earlier volumes of the series—To Err Is Human (2000), Crossing the Quality Chasm (2001), and Patient Safety (2004)—this book sets forth an agenda for improving the safety of medication use. It begins by providing an overview of the system for drug development, regulation, distribution, and use. Preventing Medication Errors also examines the peer-reviewed literature on the incidence and the cost of medication errors and the effectiveness of error prevention strategies. Presenting data that will foster the reduction of medication errors, the book provides action agendas detailing the measures needed to improve the safety of medication use in both the short- and long-term. Patients, primary health care providers, health care organizations, purchasers of group health care, legislators, and those affiliated with providing medications and medication- related products and services will benefit from this guide to reducing medication errors.
Keywords: Health and Medicine

Memorial Tributes: Volume 11 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2007)
This is the 11th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.
Keywords: Biography and Autobiography

Glut: Mastering Information Through the Ages - Alex Wright (The National Academies Press, 2007)
What do primordial bacteria, medieval alchemists, and the World Wide Web have to do with each other? This fascinating exploration of how information systems emerge takes readers on a provocative journey through the history of the information age. Today's "information explosion" may seem like an acutely modern phenomenon, but we are not the first generation—nor even the first species—to wrestle with the problem of information overload. Long before the advent of computers, human beings were collecting, storing, and organizing information: from Ice Age taxonomies to Sumerian archives, Greek libraries to Dark Age monasteries. Today, we stand at a precipice, as our old systems struggle to cope with what designer Richard Saul Wurman called a "tsunami of data." With some historical perspective, however, we can begin to understand our predicament not just as the result of technological change, but as the latest chapter in an ancient story that we are only beginning to understand. Spanning disciplines from evolutionary theory and cultural anthropology to the history of books, libraries, and computer science, writer and information architect Alex Wright weaves an intriguing narrative that connects such seemingly far-flung topics as insect colonies, Stone Age jewelry, medieval monasteries, Renaissance encyclopedias, early computer networks, and the World Wide Web. Finally, he pulls these threads together to reach a surprising conclusion, suggesting that the future of the information age may lie deep in our cultural past.
Keywords: Computers and Information Technology; Explore Science

The Third Domain: The Untold Story of Archaea and the Future of Biotechnology - Tim Friend (The National Academies Press, 2007)
The Third Domain is the untold story of how the discovery of a new form of life -- first ridiculed, then ignored for the past thirty years by mainstream scientists -- is revolutionizing science, industry, and even our search for extraterrestrial life. Classification is a serious issue for science: if you don't know what you're looking at, how can you interpret what you see? Starting with Carolus Linnaeus in the 17th century, scientists have long struggled to order and categorize the many forms of life on Earth. But by the early 20th century the tree of life seemed to have stabilized, with two main domains of life at its roots: single-celled and multi-celled organisms. All creatures fit into one of these two groups. Or so we thought. But in 1977, a lone scientist named Carl Woese determined that archaea -- biochemically and genetically unique organisms that live and thrive in some of the most inhospitable environments on Earth -- were a distinct form of life, unlike anything seen on Earth before. This shocking discovery was entirely incompatible with the long-standing classification of life as we know it. But as it turned out, archaea were not life as we know it, and the tree of life had to be uprooted once again. Now, archaea are being hailed as one of the most important scientific revelations of the 20th century. The Third Domain tells the story of their strange potential and investigates their incredible history to provide a riveting account of an astonishing discovery.
Keywords: Explore Science; Biology and Life Sciences